Fetal hydrops – a review and a clinical approach to identifying the cause. (3rd March 2020) - Dempsey, Esther; Homfray, Tessa; Simpson, John M; Jeffery, Steve; Mansour, Sahar; Ostergaard, Pia
ABSTRACT: Introduction : Fetal hydrops describes abnormal fluid accumulation in two or more extravascular fetal compartments. It is a poor prognostic sign in a fetus, and many will not survive to term. Fetal hydrops is a clinical sign rather than a diagnosis and has a multitude of different causes. Areas covered : This review focusses on nonimmune fetal hydrops. We discuss in detail the most common etiologies such as infection and chromosomal abnormalities and cover rarer presentations of congenital malformation and single-gene disorders. We present a decision tree for the investigation of affected pregnancies. Expert opinion : The current approach to the investigation of fetal hydrops largely revolves around identifying the abnormal pathophysiology via ultrasound imaging. We believe that as genomic testing of a pregnancy can be undertaken with increasing accuracy, speed, accessibility and at reduced cost, genetic testing will feature earlier in the future diagnostic pathway.